Chemical composition of Indian Ocean manganese nodules analyzed at Preuss-AG - Harald Bäcker (PANGAEA, 2023)
During the TRANSINDIK (VA07) campaign of the R/V Valdivia in the Central Indian Ocean manganese nodules were retrieved and analysed for their metal composition at Preuss-AG (PREUSSAG) by H. Bäcker. The campaign was conducted from 14 December 1973 until 23 January 1974, between Beira (Mozambique) and Singapore via Port Louis (Mauritius). This geochemical data was not published in the literature and transfered at a later stage into Scripps Institution of Oceanography (SIO) manganese nodule analysis file compiled under the direction of Jane Frazer and Mary Fisk. In this dataset, manganese nodules from the Pacific and the Indian oceans were analyzed at Preuss-AG by Atomic absorption spectrophotometry (AAS)